2022
DOI: 10.3892/ol.2022.13338
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and apoptosis regulation by G protein‑coupled estrogen receptor in glioblastoma C6 cells

Abstract: Glioblastoma is the most frequent primary tumor in the human brain. Glioblastoma cells express aromatase and the classic estrogen receptors ERα and ERβ and can produce estrogens that promote tumor growth. The membrane G protein-coupled estrogen receptor (GPER) also plays a significant role in numerous types of cancer; its participation in glioblastoma tumor development is not entirely known. The present study investigated the effect of the agonists [17β-estradiol (E2) and G1] and antagonist (G15) of GPER on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To distinguish the best response to the treatment between P-MTX NPs+P-PTX NPs and P-PTX NPs, the expressed Ki-67, VEGF, p53 and MMP-2 was quantified. Ki-67 is a marker to estimate proliferation and metastasis in tumors [98]. VEGF plays a role in angiogenesis [99] using the amount of expression as a factor to estimate the severity of GBM [64].…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish the best response to the treatment between P-MTX NPs+P-PTX NPs and P-PTX NPs, the expressed Ki-67, VEGF, p53 and MMP-2 was quantified. Ki-67 is a marker to estimate proliferation and metastasis in tumors [98]. VEGF plays a role in angiogenesis [99] using the amount of expression as a factor to estimate the severity of GBM [64].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that ERα and GPR30 decreased expression in the GBM anastrozole-treated group. The reduced number of tumor cells could be due to low estrogen alpha and GPER receptor expression and estrogen levels [ 10 , 29 ]. Further experiments are needed to quantify estrogen receptor expression in GBM-treated anastrozole mice.…”
Section: Discussionmentioning
confidence: 99%
“…A higher GPER expression in cancer cells and tissues favors cancer development, and GPER levels serve as indicators for survival prognoses, where elevated levels are related to bad outcomes. Some examples of the above have been observed in lung, prostate, cervical, glioblastoma, and breast cancer models [49][50][51][52][53]. Moreover, GPER expression is related to stemness features in breast cancer stem cells (BCSC) through phosphorylation of BCL2associated agonist of cell death (BAD) promoting cell survival, but the silencing of GPER results in a decrease in BCSC in vivo [54,55].…”
Section: Gper Expression In Cancermentioning
confidence: 99%